Newspaper Frames of Sub-Saharan Immigrants in Morocco - Dib, Salim (European Scientific Journal, ESJ, 2023)
The purpose of this article is to understand how the media framed the arrival of Sub-Saharan immigrants to Morocco. Indeed, Media consumers around the world are regularly confronted with media reports or depictions of migrants crossing the Mediterranean. However, the situation of those migrants in Morocco has grabbed media attention, especially in newspapers; hundreds of articles and reports have been written in newspapers, criticizing or denouncing the phenomenon. Although the currently available body research has tended to neglect the linguistic ways in which such media convey meaning along the side of their use of images, little attention has been paid to language-based media. In this study, I will focus on newspaper headlines because they convey the main story of the news story. The goal is to analyse the headlines of four newspapers Almassae, Assabah, Akhbar Al Yaoum, and Alahdath before the migration reform of 2013. With these objectives in mind, the article applies content analysis methodology to examine how news media framed and portrayed the arrival of ‘African’ immigrants in news headlines.